Penerapan Metode Branch and Bound dalam Optimalisasi Pendapatan Retribusi Tempat Khusus Parkir - Kamila; Cut Multahadah (STATMAT : JURNAL STATISTIKA DAN MATEMATIKA, 2025)
Keramat tinggi market is a traditional market that has a special parking area. This special parking lot is provided to accommodate the vehicles of visitors, traders, and people who move around the market. Parking users will be charged according to tariffs that have been regulated in the Regional Regulation and the parking lot retribution fee will be charged according to the tariffs that have been regulated in the Regional Regulation. This special parking lot is one of the sources of Regional Original Revenue, one of which will be used for the management of parking facilities. Parking lot management that has not been optimized will have an impact on the inefficient use of parking lots and will affect the retribution revenue that is not maximized. Inefficient use of parking lots can be caused by not knowing the optimal capacity of a parking lot, such as the high keramat market. Parking lot optimization can be done with scientific decision-making processes such as linear programming, the most common method being the simplex method. However, in some problems sometimes there are conditions where it is necessary to add artificial variables, so that with the addition of these variables the problem must be solved by more advanced methods, such as Big M. Some optimization problems whose solutions are not possible to be fractional values this method needs to be combined with a special method, one of the common methods used is the Branch and Bound method. Based on the research that has been done, the optimal income that can be obtained when all parking spaces in the keramat tinggi market are used is Rp 204,000 with a combination of providing parking spaces for motorbikes as many as 173 units, private cars as many as 5 units, and pick-up cars as many as 7 units.